Environmental and economic analysis of thermal energy storage for a district heating system in Bolungarvik - Georgia Elizabeth Hanby 1998- (2024)
Even Iceland, which is known for its renewable energy and environmental efforts, is not immune to the current climate crisis or the issue of energy insecurity. The “cold regions”, such as the Westfjords, of Iceland are impacted the most since they lack access to geothermal resources for essential heating as well as robust energy infrastructure. Not only must they rely on electricity to meet both their heating and power demand, but these regions also experience frequent outages. The current backup systems supporting the energy demand in the Westfjords during outages are highly polluting diesel fueled generators and boilers. Finding a more reliable solution for heating and reducing emissions are time-sensitive priorities for these communities. This thesis investigates sustainable technology alternatives for a district heating system in a cold region of Iceland, using the town of Bolungarvik as a case study. The study explores options including e-fuels, heat pumps, and thermal energy storage (TES), ultimately determining that TES is the most suitable technology for this specific system and challenge. The evaluation is based on criteria such as cost, accessibility, ability to provide heat during power outages, and environmental impact. The research methodology includes a comprehensive assessment of the Bolungarvik’s heating demand, prediction of the outage scenarios, and optimization of the TES tank size. Additionally, the thesis outlines the design integration of the TES system into the existing infrastructure. The analysis concludes with calculations of fuel savings, CO_2 emission reductions, cost savings, and payback period for the new system. It found that for TES tank sizes varying from 9MWh capacity to 140MWh capacity, between 45-100% of standard predicted power outages could be covered, meaning 64-173 tons of CO_2 emissions from the diesel boilers could be avoided, and 3.4-9.1 Misk could be saved on the energy bill every year. For outage scenarios with greater frequency of outage occurrences and longer outage ...